4x+3y=-8

Subtract 4x from both sides of the equation.

3y=-8-4x

Divide each term in 3y=-8-4x by 3.

3y3=-83+-4×3

Cancel the common factor of 3.

Cancel the common factor.

3y3=-83+-4×3

Divide y by 1.

y=-83+-4×3

y=-83+-4×3

Simplify each term.

Move the negative in front of the fraction.

y=-83+-4×3

Move the negative in front of the fraction.

y=-83-4×3

y=-83-4×3

y=-83-4×3

The given equation y=-83-4×3 can not be written as y=kx2, so y doesn’t vary directly with x2.

y doesn’t vary directly with x

Find the Quadratic Constant of Variation 4x+3y=-8